An Exploratory Study on the Consumer Attitudes toward Mobile Advertising Targeted To College Students in Klang Valley, Malaysia - Tan, E Teng (2011)
The rapid explosion of mobile phones along with the technological development has created a whole new marketing medium named mobile advertising. This research investigates the (1) attitudes of college students toward mobile advertising, (2) perceived risks of mobile advertising to college students, the (3) effectiveness of mobile advertising to college students, (4) responsiveness of college students, and the (5) categories of product advertising that are more acceptable to be delivered via mobile. The results, conducted on 300 college students in Klang Valley, Malaysia, showed that college students have generally (1) negative attitudes toward mobile advertising, while (2) entertainment, in formativeness, credibility, and perceived risk in mobile advertising affects their attitudes; however, (3) irritation is not influential, (4) credibility is the most important attribute affecting consumer attitudes toward mobile advertising. Besides that, the results indicate that consumers with a more favorable attitude toward an advertisement are more able to recall it than those with a negative attitude. Generally, respondents are not responsive towards mobile advertising.